just simplify both sides! easy as that!!!
= (3 - 4cos(2x) + cos^2(2x) - sin^2(2x))/8
= (3 - 4cos(2x) + cos^2(2x) - (1 - cos^2(2x)))/8
= (2cos^2(2x) - 4cos(2x) + 2)/8
= (2(cos^2(2x) - 2cos(2x) + 1))/8
= (2(cos(2x) - 1)^2)/8
= (2(1 - 2sin^2(x) - 1)^2)/8
hope I made no typos this time
TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...
Math - Solving Trig Equations - What am I doing wrong? Equation: sin2x = 2cos2x ...
trig help again i cant get any of these - sin^4cos^2x=(1/16)(1-cos 2x)(1-cos4x) ...
Trigonometry - I have some trigonometric equations to do, but I'm pretty lost, ...
trig - The expression 4 sin x cos x is equivalent to which of the following? (...
Math (Trig) - sorry, another I can't figure out Show that (1-cot^2x)/(tan^2x-1)=...
Math - Trig - Double Angles - Prove: cos4x = 8cos^4x - 8cos^2x + 1 My Attempt: ...
trig - cos@-4SIN@=1 then sin@+4cos@=
trig - Factor each expression: cos^2x- 2cosx+1 4cos^2x-1
trig - find the primary solutions. 4cos^2x-3=0 and tanx-tan^2x=0.